An Exploration of Women’s Motivations for and Experiences of Egg Freezing for Social Reasons: A Systematic Review - Hathaway, Jo (Auckland University of Technology, 2022)
Introduction: The increasing trend in developed countries of women delaying childbearing has led to an increase in oocyte cryopreservation for non-medical reasons or social egg freezing (SEF), whereby women prolong their fertility by freezing their eggs for elective or social reasons. The aim of this systematic review was to gain an understanding of the motivations for and experiences of women who choose to undergo SEF. Methods: A systematic search of English language peer-reviewed journals of five computerised databases was conducted following PRISMA guidelines. No time restrictions were set. The five databases searched were MEDLINE and CINHAL Complete (using EPSCO Health as the host platform), Scopus, PsychINFO and Google Scholar with the aim to identify articles that examined women’s motivations for and experiences of SEF such as “egg freezing”, “fertility preservation” and “experience*“. The databases were searched up until August 2, 2021. 588 studies were identified. Results: After applying inclusion criteria thirteen studies were examined in this review. Extracted data was analysed using thematic synthesis with prominent themes identified. The most common motivating factor was lack of a suitable partner while a feeling of running out of time and utilising SEF as a back-up plan or to buy options were prime considerations. While overall satisfaction with SEF was typically reported, both empowerment and loneliness were common experiences along with a need for support and honest information to ensure realistic expectations. Conclusion: The predominant reason women are electively choosing to freeze eggs is lack of finding a suitable partner with whom to have children and a sense of declining fertility. The resulting experience of freezing their eggs leads to a sense of empowerment and gratitude in having a back-up plan even if SEF might not be successful. There is a significant gap in current research with respect to New Zealand women who have undergone SEF, therefore future research into their motivations and experiences would be invaluable. It is apparent that both men and women should be given earlier information about fertility in order to be aware of age-related fertility decline.